2021
DOI: 10.1111/cobi.13849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest cover on richness of threatened fish species in Japan

Abstract: Agricultural and forest cover have opposite effects on the richness of redlisted fish species in Japanese estuaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Moreover, forests surrounding rivers constitute efficient buffers against pollution caused by other land uses, such as agriculture, because the filtering capacity of the vegetation improves water quality, which influences aquatic communities (Aguiar et al, 2011 ; Effert‐Fanta et al, 2019 ; Riis et al, 2020 ). In Japan, for example, the higher richness of red‐listed fish species was associated with high percentages of forest cover in the catchments (Lavergne et al, 2021 ). Because the highest rates of forest loss were identified in important biodiversity regions, such as in Bolivia, Brazil, Nigeria and the Lower‐Mekong River basin, we can expect an increasing global rate and a net biodiversity loss in freshwaters (Leal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, forests surrounding rivers constitute efficient buffers against pollution caused by other land uses, such as agriculture, because the filtering capacity of the vegetation improves water quality, which influences aquatic communities (Aguiar et al, 2011 ; Effert‐Fanta et al, 2019 ; Riis et al, 2020 ). In Japan, for example, the higher richness of red‐listed fish species was associated with high percentages of forest cover in the catchments (Lavergne et al, 2021 ). Because the highest rates of forest loss were identified in important biodiversity regions, such as in Bolivia, Brazil, Nigeria and the Lower‐Mekong River basin, we can expect an increasing global rate and a net biodiversity loss in freshwaters (Leal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Akamatsu et al [21] found that at all stations, more species were detected by the eDNA method than by the traditional net sampling methods for fish capture. Also, Lavergne et al [22] conducted a survey on fish biodiversity in 32 selected rivers across Japan, including the Mukawa River, using eDNA. Water samples were taken from the river mouth and 12 OTUs (out of 16 at high tide, and 17 at low tide) that were detected in the river mouth were also detected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The anadromous dace species are present in many regions of Northern Japan [19] and their biology has been studied in the Mukawa River and other rivers [20], but most species in the river have not been studied in the readily available literature. Even though the Mukawa coast is highly productive for fisheries, previous reports that included this river area were mostly limited to the downstream and coastal areas of the Mukawa River [21,22] (National Census of River Environments by Mistry of Land, Infrastructure, Transport and Tourism, Japan, http://www.nilim.go.jp/lab/fbg/ksnkankyo/; accessed on 5 April 2023), or were related to flooding and water quality effects on fish or shellfish [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In general, natural habitats have good conservation potential for specialist and narrow-ranged fish species. For example, river channels near forests can harbor more rare fish species, essentially contributing to local biodiversity 36 . Nevertheless, due to cropland expansion into the hilly and mountainous region, native and often endangered species associated with natural habitats could be replaced by cropland-associated and/or wide-ranging species, such as Osphronemus goramy or Boesemania microlepis , causing a loss of uniqueness and homogenization 33 .…”
Section: Discussionmentioning
confidence: 99%